2017
DOI: 10.3329/bjas.v45i3.31034
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ovarian types and collection techniques on the number of follicles and the quality of cumulus-oocyte-complexes in cow

Abstract: This experiment was conducted for evaluation of bovine slaughterhouse ovary, follicles, and cumulus oocyte-complexes (COCs) and to compare COCs. The collected slaughterhouse ovaries was classified as corpus luteum present (CL+) and corpus luteum absent (CL-) groups. It was found that 62.5% of the ovaries collected were CL were CL+ type. For collection of COCs, blunt dissection and aspiration techniques were performed and number of follicles collected was recorded. The higher number of follicles were dissected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
1
0
1
1
Order By: Relevance
“…The collection technique of oocytes was no significant effect (P>0.05) on oocytes quality. Similar result and same trend was reported by Mamy et al (2016) that higher percentage of COCs recovery was also recorded in blunt dissection (61.6±4.6%) than aspiration (48.6±2.9%) technique. This result lower than that of Singh et al (2019) who reported the recovery of A+B grade oocyte was 86.01% and 81.76% by aspiration and slicing technique, respectively.…”
Section: Effect Of Collection Technique On Oocyte Qualitysupporting
confidence: 91%
See 1 more Smart Citation
“…The collection technique of oocytes was no significant effect (P>0.05) on oocytes quality. Similar result and same trend was reported by Mamy et al (2016) that higher percentage of COCs recovery was also recorded in blunt dissection (61.6±4.6%) than aspiration (48.6±2.9%) technique. This result lower than that of Singh et al (2019) who reported the recovery of A+B grade oocyte was 86.01% and 81.76% by aspiration and slicing technique, respectively.…”
Section: Effect Of Collection Technique On Oocyte Qualitysupporting
confidence: 91%
“…This result supported by Habeed and Hussain (2017) who reported that the slicing method yielded significantly higher number of oocytes, and Wang et al (2007) found that when compared with many collection methods of bovine oocytes, the slicing method yield more oocytes count than the other methods. Result of this study was higher than that of Mamy et al (2016) was reported 10.5±1.5 in ovary with CL and 11.2±1.8 in ovary without CL. Nandi et al (2000) stated that when ovaries had a corpus luteum, the oocytes recovery rate decreases.…”
Section: Experiment-2 Effect Collection Technique On Quantity Of Ooccontrasting
confidence: 72%
“…Um número indeterminado de ovários coletados apresentava presença de corpo lúteo. Batista (2016) afirma que no ponto de vista morfológico, a presença de corpo lúteo não tem influência na qualidade dos oócitos imaturos, já Mamy et al (2017) afirma que a presença de corpo lúteo em ovários aspirados pode resultar em uma quantidade maior de oócitos inviáveis comparados a ovários que não apresentavam, assim tendo mais oócitos viáveis aspirados.…”
Section: Discussionunclassified